Polyethylene/sepiolite fibers. Influence of drawing and nanofiller content on the crystal morphology and mechanical properties - Alonso, Yanela Natalin (2014)
The influence of sepiolite content (1, 2, and 3 wt%) and successive drawing steps on the final properties of polyethylene/sepiolite nanocomposite fibers are reported. Particularly the effects of these variables on crystallinity, fiber macroscopic morphology, and tensile mechanical properties are analyzed applying different experimental techniques: differential scanning calorimetry, wide angle x-ray diffraction, scanning electronic microscopy, and tensile mechanical characterization. The study evidenced the important role of both sepiolite content and stretching on the crystalline morphology and mechanical properties of the nanocomposites fiber. Both variables favor the appearance of the monoclinic phase during polyethylene crystallization, and produce an increase of crystallinity degree (35 % with drawing steps and 10 % by the sepiolite incorporation in non drawing fiber). This change of crystal morphology influences mechanical properties enhancing with both sepiolite content and drawing steps. Thus, Young Modulus increases 17 times with drawing in pure PE fibers and 1.5 times because sepiolite presence. The strength shows similar behavior, but the elongation at break decreases 14 timed with draw steps and to a half by the sepiolite influence. The final properties of drawing nanocomposite fibers are so acceptable for textile applications and they content particles that enhance their moisture and odors absorptive capacities.